Improvement of Digital Technology in the Tourism Sector - NIKOLSKAYA, Elena Yurievna; LEPESHKIN, Vyacheslav Anatolievich; BLINOVA, Ekaterina Arturovna; KULGACHEV, Ivan Petrovich; ILKEVICH, Sergey Viktorovich (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).01, 2019)
The article deals with the development of approaches to the improvement of digital technology in the tourism sector. It is revealed that the improvement of digital technology in the tourism sector acquires a variety of manifestation forms, which include online purchase of ready-made tours formed by tour operators, as well as the development and implementation of mobile applications, designed, among other things, for tourists, digitalization of self-designed tours through the creation of online schools for novice travelers. It is proved that the digitalization of tourism will be accompanied by a further process of displacement of traditional companies with offline offices from the tourist market, and the development of tours designed according to the parameters individually set by each specific client. Consequently, tourist organizations, which will be able to provide to consumers best customization in the provision of tourist services, will gain competitive advantages.